Critical analysis of the aggravating circumstances of cruelty or deliberately increasing the evil of the crime by causing other evils unnecessary for its execution - Agliati Vásquez, Gonzalo; Rojas Adasme, Angelo (Revista de Estudios de la Justicia, 2024)
This paper studies the aggravating circumstance of cruelty provided for in article 12 number 4 of the Chilean Criminal Law, consisting of “deliberately increasing the evil of the crime by causing other evils unnecessary for its execution”, for which purpose its essential characteristics, the elements that constitute it and the relationships that mediate between this and other similar circumstances will be analyzed, proposing various solutions and interpretations for those aspects that seem confusing or lacking and adequate treatment by doctrine and jurisprudence.